PENERAPAN BEST PRACTICE PENGENDALIAN PADA SIKLUS PENGELUARAN PEMERINTAH - Iskandar Iskandar (Universitas Agung Podomoro, 2020)
This study analyzes the implementation of control policies and procedures in the government expenditure cycle, particularly at the central government, starting from control at the phase of commitment, goods/services received, before payment and at the time of payment. The research was conducted by analyzing the content of the regulations in the implementation of state budget expenditures.The results show that the implementation of controls in the government expenditure cycle has been fulfilled according to international practice. The application of this control is important for financial managers to ensure that the budget execution process is carried out properly.